Makna Simbolik Upacara Adat Balia Baliore Pada Suku Kaili (Kajian Semiotik) - Nurfani, Fitri (Bahasantodea, 2016)
The problem which explained in this research consisted of two things, they were ; (1) what were symbols which found in Balia Baliore traditional ceremony at Kaili tribe, (2) what were the meaning which found in symbols in Balia Baliore traditional ceremony at Kaili tribe. The objective of this research was to described the symbols which found in Balia Baliore traditional ceremony at Kaili tribe. The approach that used in this research was qualitative approach. Kind of this research which used was descriptive qualitative research. The ethod which used in this research was listening and conversation method. The data accumulation which done in this research through: (1) Observation, (2) Interview, (3) Dokumentation, (4) recording. The data analysis which used was Miles and Hubermen model through 4 steps, they were : (1) accumulation data step, (2) reduction data, (3) serving data, (4) Verification data. Research result showed that in Balia Baliore traditional ceremony at Kaili tribe that found nineteen steps, in each of step there was symbols which full meaning, there were symbols which explained in Balia Baliore traditional ceremony at Kaili tribe was verbal and nonverbal symbol. Nineteen steps of Balia Baliore traditional ceremony at Kaili tribe, they were : (1), nompairomu, (2) Nompakende joa, (3) mosore vayo, (4) mompesule manu, (5) nombangu tava kayu, (6) nangande ka ada, (7) nosinggulama pamula, (8) noisi sakaya, (9) nompopolivo sakaya, (11) mosore vayo setelah pelarungan, (12) nodungganaka tava kayu, (13) noporo ri vamba, (14) nangande ka ada kaupuna, (15) nosunggilama kaupuna, (16) nocera, (17) pray together, (18) nobagi poloya, (19) novonto potampari.